2022
DOI: 10.2147/cmar.s352308
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA SLC9A3-AS1 Promotes Oncogenesis of NSCLC via Sponging microRNA-760 and May Serve as a Prognosis Predictor of NSCLC Patients

Abstract: Background Non-small cell lung cancer (NSCLC) is a prevalent type of lung cancer worldwide. Long noncoding RNA (lncRNA) SLC9A3-AS1 is reported to play a carcinogenic role in nasopharyngeal carcinoma, but its full-scale role in NSCLC remains elusive. Methods SLC9A3-AS1 expression was detected in serum and tissue of NSLCC patients and NSCLC cell lines. The effects of SLC9A3-AS1 on NSCLC proliferation, migration and invasion were evaluated using CCK-8 and transwell assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In lung carcinomas, differential expression of lncRNAs has been observed depending on the cancer type. Representative cases are SLC9A3-AS1, reported upregulated; LINC01554 and GABPB1 reported downregulated in NSCLC tissues [166][167][168], while RBPMS-AS1 expression was found to be diminished in lung adenocarcinoma [169]. Other studies have shown the reduced expression of LINC00294 in colorectal carcinoma tissues [170], while SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2, AC026362.1 were found to be downregulated in colon cancer cell lines [171].…”
Section: Discussionmentioning
confidence: 96%

miRNAs as Interconnectors between Obesity and Cancer

González-Sánchez,
Granados-López,
López-Hernández
et al. 2024
ncRNA
“…In lung carcinomas, differential expression of lncRNAs has been observed depending on the cancer type. Representative cases are SLC9A3-AS1, reported upregulated; LINC01554 and GABPB1 reported downregulated in NSCLC tissues [166][167][168], while RBPMS-AS1 expression was found to be diminished in lung adenocarcinoma [169]. Other studies have shown the reduced expression of LINC00294 in colorectal carcinoma tissues [170], while SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2, AC026362.1 were found to be downregulated in colon cancer cell lines [171].…”
Section: Discussionmentioning
confidence: 96%

miRNAs as Interconnectors between Obesity and Cancer

González-Sánchez,
Granados-López,
López-Hernández
et al. 2024
ncRNA
“…LINC01748 plays a carcinogenic role in non−small cell lung cancer cell lines through the regulation of the microRNA−520a−5p/HMGA1 axis ( 24 ). SLC9A3-AS1 is upregulated in NSCLC, and the SLC9A3-AS1 gene knockout hinders NSCLC progression by targeting miR-760, implying that it may have a role as a new biomarker and therapeutic target of NSCLC ( 25 ). Due to the important role of lncRNAs in cancers, the implications of lncRNAs for the prognoses of LUAD patients have been widely studied ( 8 ).…”
Section: Introductionmentioning
confidence: 99%